Enhancing energy absorption of the sandwich beams with a synergetic strategy of flexible/rigid materials in re-entrant auxetic cores under flexural loading - Usta, Fatih (Springer Heidelberg, 2024)
Sandwich structures and auxetic materials have had a significant impact on various applications as energy absorbers. The purpose of this study is to manipulate the deformation mechanism of sandwich beams by using a combination of rigid and flexible material components in the core structure, thus improving their absorption capacity and flexural behavior. The effects of flexible and rigid material layer arrangements and the percentage of flexible/rigid material in the core structures were investigated by using experimental and numerical methods. Three-point bending tests of fourteen different multi-material auxetic cores and two different single material core structures were carried out using flexible TPU and rigid PLA 3D printed layers. Then, the FE analysis was performed parametrically to reveal the effects of t/l ratios of the unit cell on the flexural behavior and energy absorption performance of the sandwich beams. Experimental studies shows that the TPPP, PTPT, and TTPT hybrid core arrangements exhibit greater energy absorption capacities (9.07 J, 9.61, and 9.60 J, respectively). The deformation mechanism of the flexible and rigid materials and inclined struts of the core structures play a key role in the flexural strength and energy absorption capacities. For example, the plastic deformation mechanism could be spread over a wider area to delay the localized fractures by reinforcing the rigid auxetic core with flexible material. Also, the strength and energy absorption could be increased when the bottom layer is made of rigid material. It is recommended to avoid using adjacent layers of the flexible material because they have lower flexural strength. The parametric analysis show that the energy absorption performance could be increased within the range of similar to 5 to similar to 20% when the t/l ratio decreases.
Keywords: Sandwich beams; Multi-material; Flexible and rigid materials; Re-entrant auxetic metamaterials; Flexural behavior; Energy absorption